(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2021)
Emanuele Macaluso died in Rome at the beginning of this year. Born in Caltanissetta, he was an eminent communist leader and a valuable intellectual. His political, analytical, and polemical contribution to the debate on the Mafia and antimafia has been very worthy. A brief note in his memory is proposed, focused on his testimony to the antimafia Parliamentary Committee in November 1970, which is reported hereafter.